Low‐dose CT perfusion with projection view sharing. Issue 1 (17th November 2017) - Martin, Thomas; Hoffman, John; Alger, Jeff R.; McNitt‐Gray, Michael; Wang, Danny JJ
Abstract : Purpose: CT Perfusion (CTP) is a widely used clinical imaging modality. However, CTP typically involves the use of substantial radiation dose (CTDIvol ≥ 200 mGy). The purpose of this study is to present a low‐dose CTP technique using a projection view‐sharing reconstruction algorithm originally developed for dynamic MRI — "K‐space Weighted Image Contrast" (KWIC). Methods: The KWIC reconstruction is based on an angle‐bisection scheme. In KWIC, a Fourier transform was performed along each projection to form a "k‐space"‐like CT data space, based on the central‐slice theorem. As a projection view‐sharing technique, KWIC preserves the spatiotemporal resolution of undersampled CTP data by progressively increasing the number of projection views shared for more distant regions of "k‐space". KWIC reconstruction was evaluated on a digital FORBILD head phantom with numerically simulated time‐varying objects. The numerically simulated scans were undersampled using the angle‐bisection scheme to achieve 50%, 25%, and 12.5% of the original dose (288, 144, and 72 projections, respectively). The area‐under‐the‐curve (AUC), time‐to‐peak (TTP), and full width half maximum (FWHM) were measured in KWIC recons and compared to fully sampled filtered back projection (FBP) reconstructions. KWIC reconstruction and dose reduction was also implemented for three clinical CTP cases (45 s, 1156 projections per turn, 1 s/turn, CTDIvol 217 mGy). Quantitative perfusion metrics were computed and compared between KWIC reconstructed CTP data and those of standard FBP reconstruction. Results: The AUC, TTP, and FWHM in the numerical simzulations were unaffected by the undersampling/dose reduction (down to 12.5% dose) with KWIC reconstruction compared to the fully sampled FBP reconstruction. The normalized root‐mean‐square‐error (NRMSE) of the AUC in the FORBILD head phantom is 0.04, 0.05, and 0.07 for 50%, 25%, and 12.5% KWIC, respectively, as compared to FBP reconstruction. The cerebral blood flow (CBF) and cerebral blood volume had no significant difference between FBP and 50%, 25%, and 12.5% KWIC reconstructions ( P > 0.05). Conclusions: This study demonstrates that KWIC preserves perfusion metrics for CTP with substantially reduced dose. Clinical implementation will require further investigation into methods of rapid switching of a CT x‐ray source.